Diagnostic Accuracy of Spiral Whole‐Heart Quantitative Adenosine Stress Cardiovascular Magnetic Resonance With Motion Compensated L1‐SPIRIT. Issue 4 (6th April 2021) - Pan, Jonathan A.; Robinson, Austin A.; Yang, Yang; Lozano, Patricia Rodriguez; McHugh, Stephen; Holland, Eric M.; Meyer, Craig H.; Taylor, Angela M.; Kramer, Christopher M.; Salerno, Michael
Abstract : Background: Variable density spiral (VDS) pulse sequences with motion compensated compressed sensing (MCCS) reconstruction allow for whole‐heart quantitative assessment of myocardial perfusion but are not clinically validated. Purpose: Assess performance of whole‐heart VDS quantitative stress perfusion with MCCS to detect obstructive coronary artery disease (CAD). Study Type: Prospective cross sectional. Population: Twenty‐five patients with chest pain and known or suspected CAD and nine normal subjects. Field strength/Sequence: Segmented steady‐state free precession (SSFP) sequence, segmented phase sensitive inversion recovery sequence for late gadolinium enhancement (LGE) imaging and VDS sequence at 1.5 T for rest and stress quantitative perfusion at eight short‐axis locations. Assessment: Stenosis was defined as ≥50% by quantitative coronary angiography (QCA). Visual and quantitative analysis of MRI data was compared to QCA. Quantitative analysis assessed average myocardial perfusion reserve (MPR), average stress myocardial blood flow (MBF), and lowest stress MBF of two contiguous myocardial segments. Ischemic burden was measured visually and quantitatively. Statistical Tests: Student's t‐test, McNemar's test, chi‐square statistic, linear mixed‐effects model, and area under receiver‐operating characteristic curve (ROC). Results: Per‐patient visual analysis demonstrated a sensitivity of 84% (95% confidence interval [CI], 60%–97%) and specificity of 83% [95% CI, 36%–100%]. There was no significant difference between per‐vessel visual and quantitative analysis for sensitivity (69% [95% CI, 51%–84%] vs. 77% [95% CI, 60%–90%], P = 0.39) and specificity (88% [95% CI, 73%–96%] vs. 80% [95% CI, 64%–91%], P = 0.75). Per‐vessel quantitative analysis ROC showed no significant difference ( P = 0.06) between average MPR (0.68 [95% CI, 0.56–0.81]), average stress MBF (0.74 [95% CI, 0.63–0.86]), and lowest stress MBF (0.79 [95% CI, 0.69–0.90]). Visual and quantitative ischemic burden measurements were comparable ( P = 0.85). Data Conclusion: Whole‐heart VDS stress perfusion demonstrated good diagnostic accuracy and ischemic burden evaluation. No significant difference was seen between visual and quantitative diagnostic performance and ischemic burden measurements. Evidence Level: 2 Technical Efficacy: Stage 2